2014
DOI: 10.4236/jss.2014.29037
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Contract, Organizational Commitment and Work Satisfaction: Survey of Researchers in Chinese State-Owned Engineering Research Institutions

Abstract: This research analyzed the effect of knowledge workers' psychological contract on organizational commitment and work satisfaction. Data was collected thru a questionnaire survey given to 517 randomly selected Chinese knowledge workers in two state-owned engineering research institutions. The questionnaire contained items about the demographic profile of the respondents, psychological contract, organizational commitment and work satisfaction. The last three items were answered using a Likert rating scale rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
1
10
0
1
Order By: Relevance
“…Organizational commitment is a bond between the individuals and the organization, which lessens the possibility of the employees to leave the organization and improve their satisfaction and comfort in the organization (Matin et al, 2010). The results also support similar studies, which found that work commitment or organizational commitment has a positive and significant correlation with job satisfaction (Gangai & Agrawal, 2015;Kelly, 2015;Zhou et al, 2014).…”
Section: Seventh Work Commitment Has a Positive And Significant Inflsupporting
confidence: 89%
“…Organizational commitment is a bond between the individuals and the organization, which lessens the possibility of the employees to leave the organization and improve their satisfaction and comfort in the organization (Matin et al, 2010). The results also support similar studies, which found that work commitment or organizational commitment has a positive and significant correlation with job satisfaction (Gangai & Agrawal, 2015;Kelly, 2015;Zhou et al, 2014).…”
Section: Seventh Work Commitment Has a Positive And Significant Inflsupporting
confidence: 89%
“…Organizational commitment is an important management element that determines nurses' work performance, productivity, and impact of organizational effectiveness [6,9,10]. In this current study, nurses perceived “moderate commitment”, with higher scores observed in the “affective commitment subscale.” This suggested that the study's nurses have strong emotional attachment to their organization and to the work that they do.…”
Section: Discussionmentioning
confidence: 64%
“…A clear link between organizational commitment and job outcomes is well documented in the literature. Higher levels of organizational commitment were contributed to work effectiveness and job engagement in nurses, increased job performance, reduction in burnout [6,9,10], reduction in absenteeism and nurse turnover, and a decrease in work fatigue [11].…”
Section: Introductionmentioning
confidence: 99%
“…The roots of this challenge can be traced to organizational efforts to develop stability and job security for its human resources (Kinnie et al ., ). To this end, the organization needs to foster in its employees a sense of work commitment –a commitment to the organization’s values and goals, occupational commitment and a strong work ethic (Cohen, ; Zhou et al ., ). Providing support to this argument Ouchi () and Williamson () in their studies demonstrated that failure to develop this psychological attachment among members may require the organization to bear the increased costs of acquiring and maintaining sophisticated control systems.…”
Section: Literature Reviewmentioning
confidence: 99%